Answer: -4 1/2 , -1/2 , 1/4 , 2/3 , 2 1/3
Step-by-step explanation:
Answer:
24
Step-by-step explanation:
5(2) + 2(4 + 3)
5 x 2 + 2 x 7
10 + 14 = 24
Here you go! :D
Answer:
3 inches
Step-by-step explanation:
(14+2x) × (15+2x) = 2(14×15)
210 +30x +28x + 4x² = 420
4x² + 58x - 210 = 0
2x² + 29x - 105 = 0
2x² + 35x - 6x - 105 = 0
x(2x + 35) - 3(2x + 35) = 0
(x - 3)(2x + 35) = 0
x = 3, -35/2(not possible)
Answer:
f(n) = -n^2 -3n +5
Step-by-step explanation:
Suppose the formula is ...
f(n) = an^2 +bn +c
Then we have ...
f(1) = 1 = a(1^2) +b(1) +c
f(2) = -5 = a(2^2) +b(2) +c
f(3) = -13 = a(3^2) +b(3) +c
__
Here's a way to solve these equations.
Subtract the first equation from the second:
-6 = 3a +b . . . . . 4th equation
Subtract the second equation from the third:
-8 = 5a +b . . . . . 5th equation
Subtract the fourth equation from the fifth:
-2 = 2a
a = -1
Then substituting into the 4th equation to find b, we have ...
-6 = 3(-1) +b
-3 = b
and ...
1 = -1 +(-3) +c . . . . . substituting "a" and "b" into the first equation
5 = c
The formula is ...
f(n) = -n^2 -3n +5